The Socioeconomic Impact Assessment of Red Palm Weevil in Egypt and Saudi Arabia: An Ex-ante Evaluation - Eissa, Ali; Eldukheri, Ibrahim; Elmedani, Saad; Ijaimi, Abdalatif; Dhehibi, Boubaker; M. Oumer, Ali; Frija, Aymen; Dhraief, Mohamed Zied; Cardone, Gianluigi; Frem, Michel; Djelouah, Khaled; Yaseen, Thaer (2024)
Dates are economically, socially, culturally, and ecologically important fruit crops in the Near East and North Africa (NENA) countries. Dates also play important roles in the history, heritage, and socioeconomic life of the Arab population. They are one of the basic sources of income and employment and are among the main stable foods for local inhabitants, especially in the oases. Date palms give multiple benefits and services, including high-energy food, medicine for some diseases, shelter, microclimate, protecting plants growing under its shade from wind and high temperature, secure inputs to food industries and handicrafts, and providing by-products useful for many purposes. The Arab or the NENA Region dominates in Dates production and trade. About 75% of the global area of 1.35 million ha under date palm is in the Arab Region, producing more than 77% of the world’s production of about 9.2 million metric tons in 2020 (Ahmed and Ijaimi, 2022.